The Leadership Model in Pesantren Baitul Qur’an, Wonogiri, Central Java, Indonesia - Sunar, Sunar (LP. Ma'arif Janggan Magetan, 2022)
Pesantren Baitul Qur’an in Wonogiri, Central Java, Indonesia, is an Islamic educational institution for memorizing the Qur’an. This pesantren has succeeded in educating students to memorize the Qur’an for less than two years. This paper questions the leadership model of the leader of Pesantren Baitul Qur’an Wonogiri, who can maintain the teacher’s quality so that students can memorize the Qur’an for two years. This study aims to analyze the leadership model of Pesantren Baitul Qur’an Wonogiri using a qualitative approach. This study argues that, first, the charismatic leadership model is more widely used by pesantren directors in everyday life because it inspires and influences other teachers’ thoughts, feelings, and behaviour. Second, the democratic leadership model is more widely used by pesantren directors in the bureaucracy because every teacher has the right to make decisions to achieve teaching goals effectively and efficiently. Third, the participatory leadership model is more widely used by pesantren directors in the organizational field because it involves the community voluntarily, so all institutional agendas run well.